Pharmacological effects and safety monitoring of anabolic androgenic steroid use: differing perceptions between users and healthcare professionals - Stephanie A. Hill; W. Stephen Waring (SAGE Publishing, 2019)
Background: Androgenic anabolic steroids (AASs) have a number of licensed clinical indications but are also subject to abuse within the body building community. They have a number of potentially important adverse pharmacological effects, and users require health monitoring, including selected laboratory investigations. The extent to which AAS users are able to seek medical supervision and the ability of healthcare providers to respond to the needs of users is uncertain. The present study sought to ascertain how AAS abusers interact with healthcare providers, and self-reported knowledge among doctors regarding the healthcare effects and need for monitoring of AAS users. Methods: Questionnaires were administered, and there were 216 respondents among AAS users and 134 doctors. Results: A high proportion of AAS users cited various barriers to accessing healthcare, including 136 of 189 (72%) that reported a fear of reproach, and 107 of 194 (55%) that had avoided seeking medical advice; 137 of 193 respondents (71%) did not disclose AAS use to healthcare professionals. Doctors across a broad range of seniority stated a lack of knowledge of AASs; 130 (97%) had received no formal training, and 109 (82%) did not know which blood tests could be used for safety monitoring. Conclusions: The present study has highlighted some perceptions among the body-building community that create obstacles to them accessing appropriate safety monitoring while using AASs. Doctors may not have adequate knowledge of AASs, which may prevent them giving accurate and complete information. Further work is needed to address the barriers of communication between users and health professionals in order to facilitate better healthcare monitoring and drug safety.